(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Toddy (kallu) is a naturally fermented palm-sap beverage consumed in parts of southern India. During pregnancy, its local classification as natural, traditional, or nutritious may conflict with biomedical advice to avoid alcohol. Evidence describing how pregnant women in Telangana understand and negotiate toddy use is limited. Objective: To explore perceptions, culturally transmitted beliefs, social influences, and healthcare interactions related to toddy consumption during pregnancy among women in Sangareddy district, Telangana. Methods: A qualitative descriptive study was conducted among 16 pregnant women attending routine antenatal care at the Maternal and Child Hospital, Government General Hospital, Sangareddy. Five additional eligible women declined participation; no enrolled participant discontinued the interview. Semi-structured one-to-one interviews were conducted in Telugu or Hindi in a private room, lasted 30-45 minutes, and were audio-recorded after written and recorded verbal consent. Interviews were transcribed and translated into English by the first author, with back-translation and linguistic verification by the second and corresponding authors. Manual hybrid inductive-deductive thematic analysis was undertaken. Saturation was observed after 14 interviews and confirmed through two additional interviews. Results: Participants had a mean age of 24.3 ± 2.6 years and mean gestational age of 26.4 ± 4.4 weeks. Eleven women reported daily or nightly use, 14 consumed approximately 250 mL per occasion, and two consumed approximately 500 mL. Four interrelated themes were identified: toddy as a natural and nutritious substance distinct from alcohol; perceived maternal, fetal, and obstetric benefits; intergenerational, social, and ritual reinforcement; and limited risk awareness with weak or inconsistent healthcare influence. Participants described beliefs that toddy facilitated delivery, promoted fetal growth, improved sleep, and "cleaned" the fetus to prevent a white coating at birth. Conclusion: Toddy consumption during pregnancy in this setting was embedded within local explanatory models of health and reproduction rather than understood simply as alcohol use. Antenatal services should ask explicitly about toddy and kallu, provide clear nonjudgmental counseling, and include influential family and community members in culturally responsive prevention strategies.